Obama's wars [compact disc, abridged] - Woodward, Bob, 1943- (Simon & Schuster, 2010)
Washington Post editor Bob Woodward offers a sweeping chronicle of President Obama's clandestine decisions during his first term in office. From the Afghanistan War to secret operations in Pakistan, Obama's war on terror has been much quieter than his predecessor's. Here, Woodward sheds light on some of the closed-door conversations that have characterized Obama and his administration.